ANALISIS DAMPAK PERKEMBANGAN PARIWISATA NUSA DUA TERHADAP PENDAPATAN RUMAH TANGGA MASYARAKAT DESA ADAT BUALU KABUPATEN BADUNG - I Made Sujana; Yoviniani Yevri Yanseni; Fitria Asri Satria Dewi; Fahmi Tanjung (Nusantara Hasana Journal, 2023)
The development of tourism in the Nusa Dua area has significantly contributed to the economy of the local community, particularly the Bualu Traditional Village community. This study aims to analyze the impact of tourism development on household income in the Bualu Traditional Village community in Badung Regency. The research method used is a qualitative descriptive approach, utilizing primary data through interviews and observations, as well as secondary data from various publications and previous research. The results show that the development of the tourism industry has increased employment opportunities, encouraged the growth of micro-enterprises and tourism support services, and increased local household income. However, economic dependence on the tourism sector also creates vulnerabilities, especially during crises such as the COVID-19 pandemic. These findings demonstrate the need for community economic diversification to ensure the sustainability of household welfare in the long term.